2022
DOI: 10.1111/jocd.15520
|View full text |Cite
|
Sign up to set email alerts
|

Combination cryotherapy and intralesional corticosteroid versus steroid monotherapy in the treatment of keloids

Abstract: Background: Keloids are common and have significant negative effects on quality of life. There is a need for more effective treatment approaches for keloids. Aims:We investigated treatment outcomes of intralesional triamcinolone acetonide (IL TAC) compared with combination IL TAC and cryotherapy, including changes in pruritus, pain, and keloid size.Patients/Methods: We performed a prospective study of patients referred to one provider who treated patients with combination therapy and compared them to a histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Cryotherapy may also be used in conjunction with surgery and Intralesional injections to further decrease recurrence rates and improve esthetics and symptoms (27)(28)(29). For example, combining cryotherapy with Intralesional steroid injections results in superior outcomes compared to both alone and is more effective in reducing keloid size; Litrowski has shown that the combination of surgery and cryotherapy is a valuable treatment for keloids that is effective, convenient, well-tolerated, and does not have any significant side effects beyond local pain and hyperalgesia (30); Azzam added platelet rich plasma (PRP) injections to combine all three, using cryotherapy during surgery, and showed that triple therapy could achieve improved efficacy, a lower rate of recurrence, good cosmetic outcomes, and the absence of significant side effects (31); Stromps combined the method of cryotherapy with silicone gel sheets and found that it had the potential to significantly reduce the size of the keloid and improve its hardness, pain, and discomfort (32).…”
Section: Cryotherapy Therapymentioning
confidence: 99%
“…Cryotherapy may also be used in conjunction with surgery and Intralesional injections to further decrease recurrence rates and improve esthetics and symptoms (27)(28)(29). For example, combining cryotherapy with Intralesional steroid injections results in superior outcomes compared to both alone and is more effective in reducing keloid size; Litrowski has shown that the combination of surgery and cryotherapy is a valuable treatment for keloids that is effective, convenient, well-tolerated, and does not have any significant side effects beyond local pain and hyperalgesia (30); Azzam added platelet rich plasma (PRP) injections to combine all three, using cryotherapy during surgery, and showed that triple therapy could achieve improved efficacy, a lower rate of recurrence, good cosmetic outcomes, and the absence of significant side effects (31); Stromps combined the method of cryotherapy with silicone gel sheets and found that it had the potential to significantly reduce the size of the keloid and improve its hardness, pain, and discomfort (32).…”
Section: Cryotherapy Therapymentioning
confidence: 99%